Recommendations for the Sustainability of Patient-Centered Care’s Implementation in the Emergency Department: A Phenomenological Study - Anshori, Mahfud; Rosa, Elsye Maria; Abdelazis, Toka (Universitas Muhammadiyah Yogyakarta, 2025)
The Patient-Centered Care (PCC) approach in health services is increasingly popular. However, its implementation is still not optimal, including in the Emergency Department (ED). The challenge is weak implementation and inconsistent understanding, requiring continuous improvement efforts to maintain its sustainability. This study aims to identify recommendations for improving the implementation of PCC in the ED. Qualitative research with a phenomenological approach was used in this study. Data collection through Focus Group Discussion (FGD) was conducted with 26 informants, and in-depth interviews with 11 informants selected through purposive sampling. Data analysis used Interpretative Phenomenological Analysis (IPA), which was processed using NVIVO 14. The validity and reliability of the research were achieved by applying trustworthiness. The main findings regarding recommendations for improvement identified five themes: providing human resources according to needs, improving communication between Healthcare Professionals (HCPs), improving service regulations, consistent monitoring and evaluation, and reducing security risks. An interesting aspect of this study is its focus on Patient-Centered Care (PCC) in the Emergency Department, a complex and underexplored setting. This research underlines the importance of integrating three aspects in implementing PCC, including what should be prepared for PCC, the implementation, and supporting aspects of PCC to ensure PCC effectiveness and its sustainability in the ED.